Sustainable Bacterial Cellulose Production Using Low-Cost Fruit Wastewater Feedstocks - Cláudia Mouro; Arlindo Gomes; Ana P. Gomes; Isabel C. Gouveia (Nanomaterials, 2025)
Bacterial cellulose (BC) is a versatile biopolymer prized for its remarkable water absorption, nanoscale fiber architecture, mechanical robustness, and biocompatibility, making it suitable for diverse applications. Despite its potential, the high cost of conventional fermentation media limits BC’s scalability and wider commercial use. This study investigates an economical solution by utilizing fractions from fruit processing wastewater, refined through sequential membrane fractionation, as a supplement to commercial HS medium for BC production. BC films were thoroughly characterized using Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and assessments of mechanical properties and water holding capacity (WHC). FTIR confirmed the BC structure, while TEM validated its nanofibrillar 3D network. XRD analysis revealed a slight increasing trend in crystallinity with the addition of wastewater fractions, and DSC revealed a slight increase in thermal stability for F#6. Adding these fractions notably improved the BC films’ tensile strength, Young’s modulus, and WHC. Overall, the results underscore that fruit processing wastewater fractions can serve as a cost-efficient, eco-friendly alternative to traditional fermentation media. This approach supports circular economy principles by lowering reliance on intensive wastewater treatments, promoting waste valorization, and advancing sustainable production methods for high-value biopolymers.